Chicken soup for the soul teens talk relationships : stories about family, friends, and love - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Pub. LLC, 2008)
A compilation of true stories written by teenagers, and by adults writing about their teenage years, focusing on teen relationships with parents, friends, crushes, boyfriends and girlfriends.